Pain following cancer treatment: Guidelines for the clinical classification of predominant neuropathic, nociceptive and central sensitization pain. (2nd June 2016) - Nijs, Jo; Leysen, Laurence; Adriaenssens, Nele; Aguilar Ferrándiz, Maria Encarnación; Devoogdt, Nele; Tassenoy, An; Ickmans, Kelly; Goubert, Dorien; van Wilgen, C. Paul; Wijma, Amarins J.; Kuppens, Kevin; Hoelen, Wouter; et al.
Abstract: Background: In addition to fatigue, pain is the most frequent persistent symptom in cancer survivors. Clear guidelines for both the diagnosis and treatment of pain in cancer survivors are lacking. Classification of pain is important as it may facilitate more specific targeting of treatment. In this paper we present an overview of nociceptive, neuropathic and central sensitization pain following cancer treatment, as well as the rationale, criteria and process for stratifying pain classification. Material and methods: Recently, a clinical method for classifying any pain as either predominant central sensitization pain, neuropathic or nociceptive pain was developed, based on a large body of research evidence and international expert opinion. We, a team of 15 authors from 13 different centers, four countries and two continents have applied this classification algorithm to the cancer survivor population. Results: The classification of pain following cancer treatment entails two steps: (1) examining the presence of neuropathic pain; and (2) using an algorithm for differentiating predominant nociceptive and central sensitization pain. Step 1 builds on the established criteria for neuropathic pain diagnosis, while Step 2 applies a recently developed clinical method for classifying any pain as either predominant central sensitization pain, neuropathic or nociceptive pain to the cancer survivor population. Conclusion: The classification criteria allow identifying central sensitization pain following cancer treatment. The recognition of central sensitization pain in practice is an important development in the integration of pain neuroscience into the clinic, and one that is relevant for people undergoing and following cancer treatment.